THE IMPACT OF BANKING SERVICE DIGITIZATION ON CUSTOMER SATISFACTION AND LOYALTY IN COMMERCIAL BANKS: THE CASE OF BANQUE NATIONALE D’ALGÉRIE (BNA) - Oukal Amar, (International Journal of Innovative Technologies in Social Science, 2024)
This study aims to explore the impact of digitizing banking services on customer satisfaction and loyalty, with a focus on the Banque Nationale d’Algérie (BNA). The research adopted a descriptive-analytical methodology and employed a questionnaire to collect data from a sample of 88 customers of the Banque Nationale d’Algérie (BNA). Using SPSS software (version 25) for data analysis, the results revealed a statistically significant positive effect at the 0.05 significance level of banking service Digitization on customer satisfaction at the Banque Nationale d’Algérie (BNA). A significant positive effect was also observed on customer loyalty, indicating that digitized services enhance customer satisfaction and positively influence customer loyalty.The study also identified several factors influencing customer satisfaction and loyalty, including service quality and security. In conclusion, the study presented practical recommendations supported by procedural and implementation mechanisms to improve digitization in Algerian banks, with an emphasis on developing digitized banking services, increasing awareness of electronic banking, strengthening cyber security, and providing effective customer support services.